Understanding English Teaching & Learning Contexts and Their Importance In EFL Education (2017)
Santo Tomas University have incorporated a new dynamic to do research in “Licenciatura en Lengua Extranjera Inglés (LLEI”) because the research teachers have found two main tendencies in the research projects, which lead them to construct two Macro-projects which generate sub-projects with four different themes. From these thematic sub-projects might emerge other projects; they are call micro-projects and these are the individual projects developed by the students of the LLEI. The first macro-project is relate with the understanding and characterizing EFL in the LLEI: experiences and phenomena in the preservice teacher’s educational context, this macro-project include two important subprojects, the first one is the voices of the LLEI realities: life stories and experiences; the second subproject is “Understanding English teaching & learning contexts and their importance in EFL education”. Macro-project two, include the innovate practices in English teaching and learning practices of the LLEI preservice teachers, this macro-project also is divided in two subprojects: pedagogical innovations resulting from new approaches, methods, methodologies in the english teaching and learning, the other is pedagogical innovations that incorporate ICT (innovation, communication and technology) in EFL teaching and learning context.